Uncovering the boundary conditions of the association between concerns about falling and physical activity in adult populations: a scoping review protocol - Jason Brian Reed; Steve Amireault; Reese Colby Kerschner; Emilie Ann Chadwell; Heesoo Roh; Emily Ryan Jakob; Kelsie Jo Muller (BMJ Open)
Introduction Despite evidence of variation in how concerns about falling influence physical activity, many of the currently available knowledge syntheses merely assume that this relation is uniform across populations and contexts. Therefore, we propose a scoping review protocol to guide a summary of the bodywork that has examined the association between concerns about falling and physical activity in adult populations, with an eye on the availability of empirical evidence of moderation.Methods and analyses Studies reporting on both the concepts of concerns about falling and physical activity among samples with a mean age≥18 years will be included. Five electronic databases will be searched. We will conduct a hand search of the reference lists for all included studies and relevant knowledge syntheses and perform a citing reference search for all included studies using the Web of Science. A team of six reviewers will single-screen titles and abstracts. Two reviewers will independently assess the eligibility of each study based on a full-text examination. Results will be presented using a tree graph to display the moderating factor(s) investigated, and a ratio showing the number of time evidence for moderation was examined by the total number of investigations.Ethics and dissemination The university Human Research Protection Program determined that the proposed scoping review does not qualify as human subject research under federal human subject research regulations (IRB-2023–1656). Results will be published in a peer-reviewed journal and in the form of a one-page summary for extension programme leaders, part of a nationwide Cooperative Extension network.